Handgrip strength at midlife and familial longevity: The Leiden Longevity Study - Ling, Carolina H. Y. (Springer Netherlands, 2011)
Low handgrip strength has been linked with premature mortality in diverse samples of middle-aged and elderly subjects. The value of handgrip strength as marker of “exceptional” human longevity has not been previously explored. We postulated that the genetic influence on extreme survival might also be involved in the muscular strength determination pathway. Therefore, the objective of this study was to assess the muscle strength in a sample of middle-aged adults who are genetically enriched for exceptional survival and comparing them to a control group. We included 336 offspring of the nonagenarian from the Leiden Longevity Study who were enriched for heritable exceptional longevity, and 336 of their partners were used as controls. The Leiden Longevity study was a prospective follow up study of long-living siblings pairs together with their offspring and their partners. Handgrip strength was used as a proxy for overall muscle strength. No significant difference in handgrip strength was seen between the offspring of the nonagenarian and their partners after adjustment for potential confounders including body compositions, sum score of comorbidities, medication use, smoking and alcohol history. The main determinants of midlife handgrip strength were age, gender, total body percentage fat and relative appendicular lean mass. Although midlife handgrip strength has previously been shown to be an important prognostic indicator of survival, it is not a marker of exceptional familial longevity in middle-aged adults. This finding suggests that genetic component of susceptibility to extreme survival is likely to be separate from that of muscular strength.